Pengayaan pembelajaran dalam upaya peningkatan pengetahuan mengenai ambigus genitalia pada mahasiswi Sekolah Tinggi Ilmu Kesehatan Abdurrahman Palembang - Maritska, Ziske; Alkaf, Syifa; Inggarsih, Rara; Hafy, Zen; Purnamasari, Septi; Nindela, Rini (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Learning Enrichment to increase knowledge about ambiguous genitalia in students at STIKES Abdurrahman Palembang. Disorders of Sex Development (DSD) is a rare disease in which atypical gonads, chromosomes, and sex anatomy are found. Although it has a significant impact on both the physical and mental health of individuals with DSD, DSD cases are often undetected and underdiagnosed. Efforts to enrich material and learning to training on DSD for prospective midwife health workers are one of the real actions that can be taken to increase knowledge and awareness of DSD which is then expected to increase early identification efforts to improve the quality of life and patient outcomes. This community service activity was carried out for one semester through a series of activities in the form of guest lectures for enrichment of learning which were carried out in stages three times online for 55 students of STIKES Abdurrahman Palembang. Measurement of the level of knowledge of STIKES Abdurrahman students was carried out twice, namely before the series of activities began (pre-test) and after the activities were completed (post-test). From the results of the pre- and post-test, an increase in knowledge was obtained, which was originally only 36.4% with a sufficient level of knowledge at the time of the pre-test, to 69.1% with a sufficient level of knowledge at the time of the post-test. It is hoped that with the enrichment of learning, prospective midwives can know and understand DSD so that in the future they can improve early screening for ambiguous genitalia cases which can lead to improving the quality of life of sufferers.